2015
DOI: 10.1038/npp.2015.233
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Effects of an mGlu2/3 Receptor Antagonist and Ketamine Require AMPA Receptor Stimulation in the mPFC and Subsequent Activation of the 5-HT Neurons in the DRN

Abstract: We have reported the antidepressant effects of both metabotropic glutamate 2/3 (mGlu2/3) receptor antagonists and ketamine in several animal models, and proposed that serotonergic (5-HTergic) transmission is involved in these actions. Given that the projections from the medial prefrontal cortex (mPFC) to the dorsal raphe nucleus (DRN), where the majority of serotonin (5-HT) neurons exist, are reportedly involved in the antidepressant effects, in this study, we investigated using the forced swimming test (FST) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 39 publications
(46 reference statements)
11
117
1
1
Order By: Relevance
“…As with ketamine (Karasawa et al, 2005;Maeng et al, 2008;Fukumoto et al, 2016), we showed that the antidepressant-like efficacy of LY3020371 was prevented by blockade of AMPA receptors. AMPA receptor dependence has been reported for other mGlu2/3 receptor antagonists (Gleason et al, 2013;Fukumoto et al, 2016;Witkin et al, 2016a) and has been suggested to be (Alt et al, 2006) and remains (Abdallah et al, 2015) a leading hypothesized transducer of antidepressant efficacy. We independently confirmed this idea with the metabolomics profiling of ketamine and LY3020371.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As with ketamine (Karasawa et al, 2005;Maeng et al, 2008;Fukumoto et al, 2016), we showed that the antidepressant-like efficacy of LY3020371 was prevented by blockade of AMPA receptors. AMPA receptor dependence has been reported for other mGlu2/3 receptor antagonists (Gleason et al, 2013;Fukumoto et al, 2016;Witkin et al, 2016a) and has been suggested to be (Alt et al, 2006) and remains (Abdallah et al, 2015) a leading hypothesized transducer of antidepressant efficacy. We independently confirmed this idea with the metabolomics profiling of ketamine and LY3020371.…”
Section: Discussionmentioning
confidence: 90%
“…In summary, we have shown here that LY3020371 and oral prodrug LY3027788.HCl engender a host of antidepressantrelevant biologic effects that are in common with the known efficacious drug for treatment-resistant depression patients, ketamine, and that these effects can be predicted by drug concentrations measured in the central compartment. Multiple additional commonalties in biologic activities have been found between ketamine and other mGlu2/3 receptor antagonists (e.g., Dwyer et al, 2012Dwyer et al, , 2013Dong et al, 2016;Fukumoto et al, 2016Witkin et al, 2016a, providing an overall consistent profile across laboratories, biologic readouts, and molecules. Finally, while antidepressant efficacy for LY3020371 and its oral prodrug have been demonstrated, evidence that mGlu2/3 receptor antagonism might overcome the side effects that characterize ketamine has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one of the most consistent findings over the past several years linking the actions of antidepressants with glutamate has been the convergent preclinical and clinical data implicating amplification of AMPA receptor signaling in the initiation and regulation of antidepressant effects (Alt et al, 2006;Valentine and Sanacora, 2009), including the effects of ketamine (Maeng et al, 2008;Autry et al, 2011;Koike et al, 2011;Tizabi et al, 2012). Fukumoto et al (2016) described activation of the dorsal raphe nucleus and enhanced 5-HT signaling by either systemically administered or mPFC microinjection of LY341495 or ketamine. They concluded that the primary effect of these agents is to enhance AMPA signaling in the mPFC leading to excitatory input to the DRN and enhanced 5HT outflow.…”
Section: Rapidly Acting Antidepressant Actions Of Ly341495 Discussionmentioning
confidence: 99%
“…It is reported that the activation of AMPAR is required for ketamine’s antidepressant effects as the pretreatment of AMPAR antagonist blocked the ketamine’s antidepressant effects in rodents . Subsequently, the role of AMPAR activation in the antidepressant effects of ketamine and its two enantiomers has been replicated …”
Section: Molecular and Cellular Mechanisms Of Ketamine’s Antidepressamentioning
confidence: 99%